Using Visual Dictionary in Improving Students’ Vocabulary Achievement - Suci, Desi Wulan; Pratiwi, Aisyah; Novrieta, Dina (EEdJ: English Education Journal, 2023)
This study was focused on finding out whether using visual dictionary can improve students’ vocabulary achievement or not. The sample of this study was students of a public junior high school in Belinyu, Bangka Belitung province. Based on the result analysis (Paired Sample T-Test), it shows that the mean difference of pre-test and post-test in experimental group was 23.88, while the mean difference of pre-test and post-test in control group was 20.00. In addition, the result of difference analysis in post-test of experimental and control group showed that the value of t obtained was 3.712 which exceed the critical value of t-table 2.00 (at the significant level p< 0.05 in two tailed testing with degree of freedom 61. It means that the null hypothesis was rejected and the research hypothesis was accepted. The result of this study revealed that the post-test scores were better than the pre-test scores of experimental group. It could be seen by comparing their means. The mean of the pre-test scores was (59.00) while the mean of the post-test scores was (82.88). In line with the result, the writer suggests that the Visual Dictionary was one of the effective methods to improve students’ enthusiasm in learning English.